Efek GHRM dan Personal Moral Norm terhadap Employee Green Behavior di Sektor Perbankan - Galih Raspati; Yoki Muchsam; Mulfi Sandi Yuda; M Afrizal Maulana; Yuyun Yuniati Yuningsih; Tri Sanatha Wahyu Akbar (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The rapid environmental degradation currently compels governments and organizations to implement effective preventive measures. This study highlights the urgent need for the implementation of Green Human Resource Management (GHRM) practices and Personal Moral Norms in enhancing Employee Green Behavior within the banking sector. As governments adopt policies related to GHRM, Personal Moral Norms, and Employee Green Behavior, banks, as financial institutions, play a strategic role in promoting sustainability. The objective of this research is to analyze the effects of GHRM and Personal Moral Norms on Employee Green Behavior in the banking sector. A quantitative approach was employed, utilizing a descriptive and associative research design, involving 92 employees from the studied bank branch, with a sampling technique using a census method. Data analysis was conducted using validity and reliability tests, as well as multiple regression analysis with the aid of SPSS 24. The results indicate that GHRM and Personal Moral Norms significantly influence Employee Green Behavior, contributing to 97.8% of the variance in environmentally friendly behavior. These findings provide new insights into the importance of integrating Green values into human resource management and underscore the necessity for banks to adopt policies that support environmental sustainability. This research is expected to serve as a reference for banking institutions in formulating more effective strategies to enhance environmental awareness among employees.